INTERCEPTION OF ELECTRONIC COMMUNICATIONS IN THE WORKPLACE - Vivienne Lawack-Davids; Adriaan van der Walt (Obiter, 2022)
The need to intercept and monitor communications arose in the context of security legislation. However, the use of e-mail and the Internet in the workplace has raised concerns about the privacy of employees’ e-mail and web browsing activities. On the one hand, despite the fact that the employer’s resources are being used, employees still have an expectation that there is some measure of privacy pertaining to their communications. On the other hand, information and communications technology in the workplace raises questions about the supervision of its use. The Regulation of Interception of Communications and the Provision of Communication-related Information Act (70 of 2002 – “the RIC Act”) has recently been enacted. The effect of this Act on interception of e-mail in the workplace has been the subject of a media flurry and differences of opinion amongst information technology (IT) lawyers. Owing to uncertainties flowing from this Act, it has yet to come into operation. The aim of this note is to provide a cursory overview of the effect of the RIC Act on interception of e-mail in the workplace, to highlight the issues raised by the Act and to make recommendations on how some of these obstacles can be overcome.